Evolution of mobility sector during and beyond Covid-19 emergency: a viewpoint of industry consultancies and public transport companies - Coppola, Pierluigi; De Fabiis, Francesco (TeMA - Journal of Land Use, Mobility and Environment, 2020)
This paper presents the results of a survey carried out between April and May 2020, among a panel of chief executives of industries, consultancies in the mobility sector, and of Public Transport (PT) companies. We surveyed their expectation about the impacts of Covid-19 on urban mobility in the short-medium term and on their own business, and their opinions about the effectiveness and the sustainability of the measures proposed for coping with the emergency (e.g. incentives, public investment, regulatory measures, new supply of transport services and modes). Different views emerged between industry/consultancies, on the one hand, and PT companies, on the other. The formers show more optimism towards the future thanks to the opportunities foreseen to improve labor-efficiency and for developing new products after the crisis. On the other hand, Public Transport companies appear very much uncertain about the future and worried about the expected losses of demand and revenues, that, in the panel opinion, are far to recover the levels before the crisis (also in the long term). The measures proposed to deal with the interpersonal distances and with the reduced level of capacity are seen as effective, but some are perceived as not sustainable due to the induced increase in operating costs. Finally, poor trust in the administrative capacity is observed, to implement strong measures to manage demand peak (e.g. change in the times of the cities or of the factories) and to upgrade the PT service contracts.